The Effects of Virtual Reality Use On Millenials’ On Intention to Visit Travel Destination - Meidy Putri Utami; Wahyuni Reksoatmodjo; Tri Kuntoro Priyambodo (Indonesian Journal of Tourism and Leisure, 2022)
Virtual Reality (VR) technology in tourism is a rapidly growing product of collaboration between technology and tourism. The benefits of VR during the Covid-19 pandemic allow the technology to survive. However, previously, VR had already seen usage in various profitable aspects of tourism. For that reason, it is important to examine how VR affects an individual’s—among Indonesian millennials—interest in visiting travel destinations. This study aims to analyze the effects of using VR by observing the content quality, system quality, presence, enjoyment and satisfaction in motivating visits among millennials. A total of 371 samples were collected in this study, obtained from respondents via online-distributed questionnaires. The data were processed using the structural equation modeling (SEM) method. The results indicated that out of seven hypotheses proposed, six were accepted and one was rejected. Content quality and system quality affected satisfaction, while presence affected enjoyment and satisfaction; satisfaction and enjoyment affected intention to visit. Enjoyment does not affect satisfaction. This study also shows that content quality, system quality, presence, enjoyment indirectly affect millennials’ interest to visit travel destinations. The quality of the VR system played an important role in creating satisfaction and intention to visit among millennials, so travel destination managers need to consider this.